MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA SISWA KELAS IV SDN 111/I MUARA BULIAN - Febriani; Ahmad Hariandi; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is a class action research (PTK) using the team games tournamen learning model aims to describe the process of increasing student learning motivation in class IV Pancasila education subjects at SDN 111/1 Muara Bulian. This research process begins with observation and documentation. Data was analysed quantitatively and qualitatively. This research was conducted in two cycles, with four stages: planning, implementation, observation, and reflection. Based on the results of the study, applying the Teams Games Tournament (TGT) learning model to Pancasila education learning was able to increase student learning motivation. This is because students experience increased motivation by paying attention to each indicator of motivation in learning can be seen in each meeting cycle. The results of this study were cycle I meeting I was 49.72% in the ‘Low’ category, cycle I meeting II was 58.8% in the ‘Fair’ category with an increase of 8.4%. In cycle II, the first meeting was 70% with the ‘Good’ category with an increase of 12% and cycle II meeting II 74% increased by 4%. From the results of this study it can be concluded that the team games tournamen learning model can increase the learning motivation of fourth grade students of SDN 111/1 Muara Bulian. This is evidenced by the increase in each indicator of student motivation in each meeting cycle.